Role of Chlamydia pneumoniae in community-acquired pneumonia in hospitalized Jordanian adults - Al-Aydie, Suzan N; Obeidat, Nathir M; Al-Younes, Hesham M (The Journal of Infection in Developing Countries, 2016)
Introduction: This study investigated the role of Chlamydia pneumoniae in the etiology of community-acquired pneumonia (CAP) in Jordanian adults. Methodology: Eighty hospitalized CAP patients and 110 healthy adults were enrolled. Overall prevalences of C. pneumoniae IgG antibodies in sera and the rate of acute infection were estimated, using the microimmunofluorescence method (MIF), at titers of 1:16 and 1:512, respectively. Moreover, a nested polymerase chain reaction (PCR) was used to detect C. pneumoniae DNA in nasopharyngeal and blood Buffy coat samples. Results: Overall chlamydial IgG prevalence was higher in CAP cases than controls (70% versus 61.8%). Similarly, higher rate of acute infection was found in patients than in controls (16.3% versus 5.5%). By focusing on subjects testing positive at 1:16, acute infection was detectable in 23.2% of CAP cases, compared with 8.8% of seropositive controls. Chlamydial DNA was confirmed in 8.2% and 8.8% of nasopharyngeal specimens from controls and patients, respectively. Moreover, 10.9% and 7.5% of Buffy coats from controls and cases, respectively, were PCR-positive. When performances of both assays for detection of the pathogen were assessed, the sensitivities of MIF and PCR were low and comparable. However, MIF demonstrated higher specificity, positive predictive value, and negative predictive value than PCR. Conclusions: MIF-based data indicate that C. pneumoniae could be a potential causal agent of CAP in Jordan. This study may serve as a basis to elucidate the exact role C. pneumoniae and other co-infecting pathogens in the etiology of respiratory tract disease.